Physicochemical Studies of Complex Fertilizers Obtained from The Decomposition of Guliob Phosphorites - Panjiyev Olimjon Kholliyevich; Panjiyev Arzikul Kholliyevich; Nurmatov Umarali; Ibatov Rakhmat Asrorovich (Genius Publishing Group, 2021)
Currently, the problem is the lack of phosphorus fertilizers and the inability to fully supply them. This article suggests using Guliob phosphorites to get rid of this problem. The author also analyzes complex fertilizers obtained from the decomposition of Guliob phosphorites using various physicochemical researchs.
Keywords: Phosphate; ores; calcium nitrate; calcium hydrophosphate